Newly identified climatically and environmentally significant high-latitude dust sources - Meinander, Outi; Dagsson-Waldhauserova, Pavla; Amosov, Pavel; Aseyeva, Elena; Atkins, Cliff; Baklanov, Alexander; Baldo, Clarissa; Barr, Sarah L.; Barzycka, Barbara; Benning, Liane G.; Cvetkovic, Bojan; Enchilik, Polina; et al. (Copernicus Publ., 2022)
Dust particles from high latitudes have a potentially large local, regional, and global significance to climate and the environment as short-lived climate forcers, air pollutants, and nutrient sources. Identifying the locations of local dust sources and their emission, transport, and deposition processes is important for understanding the multiple impacts of high-latitude dust (HLD) on the Earth's systems. Here, we identify, describe, and quantify the source intensity (SI) values, which show the potential of soil surfaces for dust emission scaled to values 0 to 1 concerning globally best productive sources, using the Global Sand and Dust Storms Source Base Map (G-SDS-SBM). This includes 64 HLD sources in our collection for the northern (Alaska, Canada, Denmark, Greenland, Iceland, Svalbard, Sweden, and Russia) and southern (Antarctica and Patagonia) high latitudes. Activity from most of these HLD sources shows seasonal character. It is estimated that high-latitude land areas with higher (SI ≥0.5), very high (SI ≥0.7), and the highest potential (SI ≥0.9) for dust emission cover >1 670 000 km2, >560 000 km2, and >240 000 km2, respectively. In the Arctic HLD region (≥60∘ N), land area with SI ≥0.5 is 5.5 % (1 035 059 km2), area with SI ≥0.7 is 2.3 % (440 804 km2), and area with SI ≥0.9 is 1.1 % (208 701 km2). Minimum SI values in the northern HLD region are about 3 orders of magnitude smaller, indicating that the dust sources of this region greatly depend on weather conditions. Our spatial dust source distribution analysis modeling results showed evidence supporting a northern HLD belt, defined as the area north of 50∘ N, with a “transitional HLD-source area” extending at latitudes 50–58∘ N in Eurasia and 50–55∘ N in Canada and a “cold HLD-source area” including areas north of 60∘ N in Eurasia and north of 58∘ N in Canada, with currently “no dust source” area between the HLD and low-latitude dust (LLD) dust belt, except for British Columbia. Using the global atmospheric transport model SILAM, we estimated ...